Richness and morphometrics characteristics of birds of understory forest in Varillal Alto Seco of the Allpahuayo Mishana National Reserve, Peru - Acosta Diaz, Arturo (2019)
The understory birds in the Alto Seco Varillal of the Allpahuayo-Mishana National Reserve (RNAM) in Peru were evaluated between January and May 2016 to determine their richness and morphometric characteristics applying direct observation, auditory recognition and capture using mist nets. The richness was composed of 12 orders, 18 families and 122 species, where the order of Passeriformes recorded 13 families and Thamnophilidae 23 species. Species richness among “varillales” varied between 85 species (varillal B) and 51 species (varillal C). The nonparametric indices indicate that the specific richness of birds observed (122 species) was always lower than expected (CHao 1 with 130 species, CHao 2 with 133 species, Bootstrap with 136 species and Jackknife 1 with 149 species) and the same trend was observed with the Clench curve with 166 expected species, while the Simpson diversity index varied between 0.96 and 0.98, Shannon-Winner between 3.69 and 4.30 and Margalef between 10.31 and 16.93, indicating a high diversity of birds. The morphometric data of the species captured showed low variability with respect to that reported for other places, except Geootrygon montana, Celeus elegans, Pithys albifrons, Schistocicla leucostigma, Xiphorhynchus elegans, Attila spadiceus and Manacus manacus that presented greater variability. It is concluded that the understory of the Alto Seco Varillal has high richness of birds in the RNAM.